2011
DOI: 10.1007/s11030-011-9311-8
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the binding modes of human β3-adrenergic receptor agonists with ligand-based and receptor-based methods

Abstract: Agonists of β(3)-adrenergic receptor (AR) have been thought as potential drugs for the treatment of obesity, type II diabetes, and overactive bladder. In order to clarify the essential structure-activity relationship and the detailed binding modes of β(3)-AR agonists as well as to identify new lead compounds activating β(3)-AR, ligand-based and receptor-based methods were applied. The pharmacophore models were developed based on 144 β(3)-AR agonists. Meanwhile, the homology model of the β(3)-AR was built based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…The predicted binding mode demonstrated that both F308 6.51 and F309 6.52 were located in the binding pocket and that they had hydrophobic interactions with BRL ( Figure 3A), which are consistent with our results and the newly reported observations [36] . However, through the homology and molecular docking studies, we could not conclude that F309…”
Section: Functional Analysis Of F309supporting
confidence: 92%
“…The predicted binding mode demonstrated that both F308 6.51 and F309 6.52 were located in the binding pocket and that they had hydrophobic interactions with BRL ( Figure 3A), which are consistent with our results and the newly reported observations [36] . However, through the homology and molecular docking studies, we could not conclude that F309…”
Section: Functional Analysis Of F309supporting
confidence: 92%
“…The design of potent, selective human β 3 -AR agonists has been traditionally focused on the compounds in which aryloxypropanolamine or arylethanolamine pharmacophore has been attached to substituted (hetero)aryl fragment through ethane-1,2-diyl spacer. 17,18 Additionally, in terms of identification of the essential features for β 3 -AR agonistic activity has been previously observed, that the free secondary amino and hydroxyl groups within such molecules have been regarded as essential structural requirements. 19 An insight into chemical structure of currently investigated aryloxypropanolamine-based compounds BL-14S2-BL-44S2 ( Table 1) has revealed that they have met the criteria mentioned above.…”
Section: Resultsmentioning
confidence: 99%
“…Jin model [30] 144 (35, 109) H, PI, RA, H, HBA Catalyst v4.10 Saxena-Roy model [31] 175 (51, 124) HBD, PI, H, NI, H Discovery Studio v2.0 Ujiantari model 95 (19,76) H, HBD, HBA, HBD, PI, H LigandScout v3.12 [a] HBD: hydrogen bond donor, HBA: hydrogen bond acceptor, PI: positive ionizable, NI: negative ionizable, H: hydrophobic interaction, RA: ring aromatic, HpAI: hydrophobic aliphatic, HpAr: hydrophobic aromatic. [b] The model was used in the virtual screening process, but without biological testing of hits.…”
Section: Pharmacophore Modeling and Virtual Screeningmentioning
confidence: 99%
“…However, none of those studies involved experimental in vitro validation of predicted hits. [27][28][29][30][31] Therefore, this study aimed to perform pharmacophore-based virtual screening and also confirm the biological activity of selected hit compounds.…”
Section: Introductionmentioning
confidence: 99%